The ethnographic self: Fieldwork and the representation of identity - Coffey, Amanda (London Sage, 1999)
What are the relationships between the self and fieldwork? How do personal, emotional and identity issues impact upon working in the field?This book argues that ethnographers, and others involved in fieldwork, should be aware of how fieldwork research and ethnographic writing construct, reproduce and implicate selves, relationships and personal identities. All too often research methods texts remain relatively silent about the ways in which fieldwork affects us and we affect the field. The book attempts to synthesize accounts of the personal experience of ethnography. In doing so, the author makes sense of the process of fieldwork research as a set of practical, intellectual and emotional accomplishments. The book is thematically arranged, and illustrated with a wide range of empirical material.